Recent Developments in The Influencing Variables of Hydrodistillation for Enhancing Essential Oil Yields in Indonesia: A Brief Review - Dewantoro, Awaly Ilham; Alifia, Alvita Rahma; Handini, Tanti; Qolbi, Latifah Zainul; Ihsani, Dita Amelia; Nurliasari, Desy (Universitas Sanata Dharma, 2024)
Hydrodistillation is widely known as the simplest essential oils (EOs) isolation technique and is widely used by small-scale producers, such as in Indonesia. The main characteristic of hydrodistillation is the plant-source material of EOs soked in water, followed by boiling and diffusion. Variuos problems arise from the use of hydrodistillation, including the possibility of overheating, degradation of EOs because of the long heating time, difficulty in controlling the heat, and a slow process. The aim of this study was to review the recent developments in hydrodistillation technology that have been developed in Indonesia to improve the quality and yield of EOs. Bibliometric analysis trhough the Methodi Ordinatio was used to compile a systematic review of prior studies in the recent decade regarding the application of hydrodistillation in Indonesia. The results showed that five plant-source commodities were extensively isolated consisting of citrus, lemongrass, cinnamon, nutmeg, and ginger. Furthermore, this study investigated the variables that influnce the hydrodistillation process for EOs isolation. The variables were often evaluated according to the results are distillation time, pretreatment of raw materials, feed-to-solvent ratio, particle size, growth place, and plant developmental stage. A future perspective was considered and outlined to carroed out further novel study and development strategies. Keywords: Bibliometric analysis, Hydrodistillation, Plant commodities, Process variables, Pretreatment.